COORPORATE SOSIAL RESPONBILITY (CSR) TAMBANG BATU BARA DAN PENGARUHNUYA TERHADAP KESEJAHTERAAN MASYARAKAT DI KABUPATEN BERAU KALIMANTAN TIMUR - Nuryanti Mustari; Marsha Putri Maulia; Muh. Yoghy Wana Putra; Herman Herman (Institut Pemerintahan Dalam Negeri, 2023)
Corporate Social Responsibility or CSR is a concept or action taken in the world of business or industry as a sense of responsibility that will be aimed at social and the surrounding environment. In the community development program, PT. Berau Coal places CSR together with other activities, this is an effort to maintain the continuity of the company's business by focusing on the unity of aspects and economic, social and worker safety. This study aims to determine the implementation of Coal Mining CSR in PT. Berau Coal in Berau Regency. This study used descriptive quantitative methods, namely procedures for expressing facts that accommodate the form of numbers in the management of statistical data and as a complement to quantitative data. The object of this research was the Central Bureau of Statistics for Berau Regency, employees and the community who live near the mining area in Rantau Panjang Village, Sambaliung District, Berau Regency. The data analysis technique used a simple linear regression test to find out two variables between the independent variable X and the dependent variable Y which will be subjected to the statistical regression analysis procedure. The results of the study showed that the implementation of corporate social responsibility or CSR related to community welfare includes the Education, Health, Social Economy and Environmental Culture sectors.